BRIDGE −1 TRIAL: BReak Interval Delayed surgery for Gastrointestinal Extraperitoneal rectal cancer, a multicentric phase III randomized trial. (May 2022) - Chiloiro, Giuditta; Meldolesi, Elisa; Corvari, Barbara; Romano, Angela; Barbaro, Brunella; Coco, Claudio; Crucitti, Antonio; Genovesi, Domenico; Lupattelli, Marco; Mantello, Giovanna; Menghi, Roberta; Falchetto Osti, Mattia; et al.
Highlights: The lengthening of the surgical interval has a positive impact on pathological complete response (pCR) rate. Lengthening the surgical interval from the end of preoperative chemoradiation is not detrimental to survival outcomes in locally advanced rectal cancer. Prospective validation of the impact of surgical interval lengthening on complete response and survival outcomes in a randomized trial. Abstract: Design: Neoadjuvant chemoradiotherapy (nCRT) followed by surgery is the standard of care for locally advanced rectal cancer (LARC). Several studies have shown a correlation between a longer interval between the end of nCRT and surgery (surgical interval - SI) and an increased pathological complete response (pCR) rate, with a maximum obtained between 10 and 13 weeks. The primary endpoint of this multicenter, 2-arm randomised trial is to investigate SI lengthening, evaluating the difference in terms of complete response (CR) and Tumor Regression Grade (TRG)1 rate in the two arms. Secondly, the impact of SI lengthening on survival outcomes and quality of life (QoL) will be investigated. Methods: Intermediate-risk LARC patients undergoing nCRT will be prospectively included in the study. nCRT will be administered with a total dose of 55 Gy in 25 fractions on Gross Tumor Volume (GTV) plus the corresponding mesorectum of 45 Gy in 25 fractions on the whole pelvis. Chemotherapy with oral capecitabine will be administered continuously. The patients achieving a clinical major or complete response assessed at clinical-instrumental re-evaluation at 7–8 weeks after treatment completion, will be randomized into two groups, to undergo surgery or local excision at 9–11 weeks (control arm) or at 13–16 weeks (experimental arm). Pathological response will be assessed on the surgical specimen using the AJCC TNM v.7 and the TRG according to Mandard. Patients will be followed up to evaluate toxicity and QoL. The promoter center of the trial will conduct the randomization process through an automated procedure to prevent any possible bias. For sample size calculation, using CR difference of 20% as endpoint, 74 patients per arm will be enrolled. Conclusions: The results of this study may prospectively provide a new time frame for the clinical re-evaluation for complete/major responders patients in order to increase the CR rate to nCRT. Trial registration: ClinicalTrials.gov Identifier: NCT03581344.